A Qualitative Analysis of Korean Students’ Awareness of Motivational Macro Strategies (Journal of Education and Development, 2018)
Motivation remains a topic of great importance in the field of EFL. Numerous studies have highlighted the linkage between the use of motivational strategies and student achievement in foreign language acquisition. In 2017 a study carried out by Heinz and Kobylinski found significant differences between the ways in which Korean students rated the use of motivational strategies by native English-speaking English teachers and native Korean speaking English teachers. These differences were explored primarily through the use of a 47 question survey utilizing a 5-point Likert scale and some limited qualitative interviews. As the survey provided strategies for comparison, the question arose whether students recalled such differences due to prompting and how a more open-ended investigation might better explain these findings. As such open-ended interviews were carried out with 21 Korean students whose backgrounds were similar to the students in the previous study. The results not only confirmed previous findings but provided considerable context as to why strategy implementation differs between the two groups. The most significant differences described were related to creating a pleasant classroom environment and familiarizing students with L2 related values. Interviewees described a high stress environment within the Korean educational system and suggested that differences between the two groups were more pronounced when native English-speaking English teachers were teaching in an international or American setting.